2000
DOI: 10.1021/ol005953g
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific and Regioselective Rhodium-Catalyzed Allylic Alkylation:  Diastereoselective Approach to Quaternary Carbon Stereogenic Centers

Abstract: The enantiospecific and regioselective rhodium-catalyzed allylic alkylation of a series of chiral nonracemic allylic carbonates, followed by ozonolysis and reductive lactonization, provides a convenient route to optically active gamma-lactones. Sequential alkylation and reductive alkylation furnished the alpha-quaternary-beta-ternary substituted gamma-lactone derivative as a >/=10:1 mixture of diastereoisomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…For example, the application of this reaction to a range of enantiomerically enriched allylic carbonates with the sodium salt of methyl phenylsulfonylacetate provides products that represent important synthons for targetdirected synthesis (Tab. 10.1) [17].…”
Section: Rhodium-catalyzed Allylic Alkylation Reaction With Stabilizementioning
confidence: 98%
See 1 more Smart Citation
“…For example, the application of this reaction to a range of enantiomerically enriched allylic carbonates with the sodium salt of methyl phenylsulfonylacetate provides products that represent important synthons for targetdirected synthesis (Tab. 10.1) [17].…”
Section: Rhodium-catalyzed Allylic Alkylation Reaction With Stabilizementioning
confidence: 98%
“…(17) 90(13)84 (45) 86 (26) 95 95 95 95 80 75 70 70 a) Numbers in parenthesis refer to % ee. b) One equivalent.…”
mentioning
confidence: 99%
“…Rh-catalysed allylic substitutions have unique features and can be highly regioselective 12 . Evans and co-workers reported that alkylations with stabilized nucleophiles 13,14 and arylations with non-stabilized aryl zinc nucleophiles 15 are highly stereospecific processes-overall retention of configuration is observed with stabilized nucleophiles and overall inversion occurs with arylzinc compounds, so that highly enantiomerically enriched compounds can be obtained by starting from single-enantiomer allylic coupling partners (Fig. 1c).…”
mentioning
confidence: 99%
“…Nach oxidativer Addition des Allylfragments an den Katalysator wird, insbesondere bei der palladiumkatalysierten Variante, ein h 3 -Allylfragment als reaktives Intermediat angenommen, das h 3 -h 1 -h 3 -Umlagerungsreaktionen eingeht. [2] Rhodium- [3][4][5][6] und eisenkatalysierte allylische Alkylierungen [7] sind von großem Interesse, da in vielen Fällen das ipso-Substitutionsprodukt als Hauptisomer erhalten wurde. Eine mögliche Erklärung für diese Regioselektivität und die Übertragung der Enantioselektivität würde ein s-Allylintermediat mit schwacher p-Koordination liefern (Schema 1 oben).…”
unclassified